ANTIDIABETIC ACTIVITY OF POWDER AND ETHANOLIC EXTRACT OF ANTLION (Myrmeleon sp.) ON WISTAR STRAIN WHITE MALE RATS WITH GLUCOSE PRELOAD - Hamidah Haryanti Rahma; Elza Sundhani; Nunuk Aries Nurulita (UPT Penerbitan Universitas Jember)
Diabetes mellitus (DM) is a group of metabolicdiseases characterized by hyperglycemia. It occursbecause abnormalities in insulin secretion, insulinaction, or both (Gustaviani, 2006). Diabetestreatment is generally done through regular insulininjections and delivery of oral antidiabetic drug suchas sulfonylurea class, biguanide, thiazolidinedion andmeglitinida which have some side effects likeheadache, dizziness, nausea, anorexia andpermanent organ damage. More over, they are alsoexpensive. People start taking treatment intraditional way natural materials, such as antlion(Myrmeleon sp.,) to lower blood glucose level (Lee etal., 2007).Previous research showed that the young antlionmethanolic extract of had the highest inhibitoryactivity toward α-glucosidase enzyme, was 22.81%(Faiz, 2008). Giving combination of Antlion andbananas for 14 days could decrease blood glucoselevels at a dose of 0,01ml / 200g (Tyas 2006).This study has examined the antidiabetic effects ofthe powder and ethanolic extract of antlion(Myrmeleon sp.) on blood glucose level of Wistarmale rats were burdened by glucose.